2008
DOI: 10.1007/s00431-008-0876-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of leptin, soluble leptin receptor, resistin, and insulin secretory dynamics in the pathogenesis of hypothalamic obesity in children

Abstract: Hypothalamic obesity seems to be related to both dysregulated afferent (leptin) and efferent (insulin) neural outputs through the autonomic nervous system resulting in energy storage as fat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 29 publications
1
29
0
3
Order By: Relevance
“…Two causes could account for this: on the one hand, the higher FM of CP patients and on the other hand, a leptin resistance caused by the damage of the hypothalamus (31).…”
Section: Discussionmentioning
confidence: 99%
“…Two causes could account for this: on the one hand, the higher FM of CP patients and on the other hand, a leptin resistance caused by the damage of the hypothalamus (31).…”
Section: Discussionmentioning
confidence: 99%
“…Guran T et al have shown that leptin levels corrected for body mass index (BMI) are higher in patients with hypothalamic obesity than in simple obesity, indicating that there a disruption of responses to leptin and more severe leptin resistance in hypothalamic obesity [21]. A disturbed feedback mechanism from the hypothalamic leptin receptors to the adipose tissue can be assumed, including a loss of leptin feedback inhibition on neuropeptide Y and Agouti-related peptide which are orexigenic hormones [21].…”
Section: Hyperleptinemiamentioning
confidence: 99%
“…A disturbed feedback mechanism from the hypothalamic leptin receptors to the adipose tissue can be assumed, including a loss of leptin feedback inhibition on neuropeptide Y and Agouti-related peptide which are orexigenic hormones [21].…”
Section: Hyperleptinemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Some reports have documented alterations in human growth hormone (hGH) and insulin levels at the onset, whereas others have described endocrine disorders of hypothalamic insufficiency resulting from surgery of the tumor. 5 The latest patient admitted to our hospital with this syndrome was diagnosed with a low-grade astrocytoma, which was not resected due to its location. After an initial period of tumor growth, the patient responded well to second-line chemotherapy, with a reduction in tumor size, clinical improvement, and gradual weight recovery.…”
mentioning
confidence: 99%